HUBUNGAN ANTARA KREATIVITAS DENGAN HASIL BELAJAR KOGNITIF SISWA KELAS X IPA BASIC SMA ABC PADA PEMBELAJARAN MATEMATIKA [ON THE RELATIONSHIP BETWEEN CREATIVITY AND COGNITIVE LEARNING OUTCOMES OF GRADE 10 BASIC SCIENCE HIGH SCHOOL STUDENTS IN MATHEMATICS LEARNING] - Banjarnahor, Evander; Winardi, Yonathan; Dirgantoro, Kurnia Putri Sepdikasari (JOHME: Journal of Holistic Mathematics Education, 2018)
Creativity is a very important aspect of learning, including learning mathematics, because creativity helps students in problem solving. This article is an associative quantitative correlational research to determine the relationship between creativity and cognitive learning outcomes of students in grade 10 (basic science track) at a high school in Tangerang. Data collection techniques were carried out by questionnaires and tests. The questionnaire obtained data on the students' creativity and the tests gathered data on the students' cognitive learning outcomes. The results of the study showed that the creativity of the students were categorized as (1) high (14.29%) , (2) quite high at 55.10%, (3) fair (26.53%) and (4) low (4.08 %). For the cognitive learning outcomes, students were categorized as (1) high (44.90%), (2) quite high (28.57%), (3) average (22.45%) and (4) low (4.08%). This study shows that there is a positive and significant association (r = 0.372, p = 0.004) between creativity and cognitive learning outcomes of these grade 10 students presented by the regression equation Y = 9.908 + 0.638 X.BAHASA INDONESIA ABSTRACT: Kreativitas merupakan salah satu aspek yang sangat penting dalam pembelajaran, termasuk dalam pembelajaran matematika, karena kreativitas membantu siswa dalam pemecahan masalah.  Artikel ini merupakan suatu penelitian kuantitatif asosiatif korelasional untuk mengetahui ada tidaknya hubungan antara kreativitas dengan hasil belajar kognitif siswa kelas X IPA Basic SMA ABC Tangerang. Teknik pengumpulan data dilakukan dengan angket dan tes. Angket digunakan untuk memperoleh data mengenai kreativitas siswa dan tes untuk memperoleh data mengenai hasil belajar kognitif siswa. Hasil penelitian ini menunjukkan bahwa kreatifitas siswa kelas X IPA Basic SMA ABC Tangerang dapat dikategorikan sebagai (1) tinggi (14,29%), (2) cukup tinggi (55,10%), (3) rata-rata (26,53%) dan (4) rendah (4,08%). Sedangkan hasil belajar kognitif siswa kelas X IPA Basic SMA ABC  Tangerang dapat dikategorikan sebagai (1) tinggi (44,90%), cukup tinggi (28,57%), rata-rata (22,45%) (4) rendah (4,08%). Penelitian ini menunjukkan bahwa terdapat asosiasi positif dan signifikan ( r = 0.372, p = 0.004) antara kreativitas dengan hasil belajar kognitif siswa kelas X IPA Basic SMA ABC, yang dinyatakan dengan persamaan regresi.